2010
DOI: 10.1007/s10620-009-1098-4
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of Alcohol Dehydrogenase (ADH) Isoenzymes and Aldehyde Dehydrogenase (ALDH) Measurement in the Sera of Colorectal Cancer Patients

Abstract: The results suggest a potential role for ADH I as marker for colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
(23 reference statements)
1
12
0
Order By: Relevance
“…The area under the ROC curve indicates the clinical usefulness of tested substances. The larger area under the ROC curve signifies a better tumor marker [18]. In this study, the ADH IV (0.67) area under the ROC curve was smaller than tumor markers (CEA, 0.79;), TIMP-1 (0.83) and MMP-9 (0.71).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The area under the ROC curve indicates the clinical usefulness of tested substances. The larger area under the ROC curve signifies a better tumor marker [18]. In this study, the ADH IV (0.67) area under the ROC curve was smaller than tumor markers (CEA, 0.79;), TIMP-1 (0.83) and MMP-9 (0.71).…”
Section: Discussionmentioning
confidence: 51%
“…Previously, we have found that serum activities of ADH I and ADH total were higher in colorectal cancer (CRC) patients than in healthy subjects and ADH I could be helpful for diagnostic of CRC [18]. This is the first study showing all the diagnostic criteria for alcohol dehydrogenase and aldehyde dehydrogenase in gastric cancer patients.…”
Section: Discussionmentioning
confidence: 73%
“…The differential genes and metabolites on the colorectal cancer data set were mostly located in the pyruvate and lactate metabolism region of the pathway, which was successfully identified by Subpathway-GM (Supplementary Figure S1). Many studies also indicated that this region was closely related to energy demand of colorectal cancer tissues (17,18,34). …”
Section: Resultsmentioning
confidence: 99%
“…Isoenzymes of class I ADH are encoded by ADH1A , ADH1B , and ADH1C , whereas class II, III, IV, and class V ADH are encoded by ADH4 , ADH5 , ADH6 , and ADH7 , respectively 19. Numerous studies have shown that the serum levels of class I ADH are a potential diagnostic marker in multiple cancers, including renal cell,20 brain,21 colorectal,22 endometrial,23 and cervical cancers 24. Similar diagnostic values can also be observed in class III ADH for pancreatic cancer,8 and class IV ADH for esophageal25 and gastric cancers 26.…”
Section: Discussionmentioning
confidence: 99%